Magnetic resonance imaging: Review of imaging techniques and overview of liver imaging - Maniam, Santhi (Baishideng Publishing Group Co., Limited, 2010)
Magnetic resonance imaging (MRI) of the liver is slowly transitioning from a problem solving imaging modality to a first line imaging modality for many diseases of the liver. The well established advantages of MRI over other cross sectional imaging modalities may be the basis for this transition. Technological advancements in MRI that focus on producing high quality images and fast imaging, increasing diagnostic accuracy and developing newer function-specific contrast agents are essential in ensuring that MRI succeeds as a first line imaging modality. Newer imaging techniques, such as parallel imaging, are widely utilized to shorten scanning time. Diffusion weighted echo planar imaging, an adaptation from neuroimaging, is fast becoming a routine part of the MRI liver protocol to improve lesion detection and characterization of focal liver lesions. Contrast enhanced dynamic T1 weighted imaging is crucial in complete evaluation of diseases and the merit of this dynamic imaging relies heavily on the appropriate timing of the contrast injection. Newer techniques that include fluoro-triggered contrast enhanced MRI, an adaptation from 3D MRA imaging, are utilized to achieve good bolus timing that will allow for optimum scanning. For accurate interpretation of liver diseases, good understanding of the newer imaging techniques and familiarity with typical imaging features of liver diseases are essential. In this review, MR sequences for a time efficient liver MRI protocol utilizing newer imaging techniques are discussed and an overview of imaging features of selected common focal and diffuse liver diseases are presented.